The first documented record of Tibetan Lark Melanocorypha maxima for Nepal - Kusi, N; Werhahn, G (Oriental Bird Club, 2016)
In July and August 2015 we carried out research on wolves Canis sp. Bos mutus around the Gyau valley, in the remote upper Humla district of north-west Nepal, which is located in the south-west corner of the Tibetan plateau, bordering the Tibetan Autonomous Region of China to the north. This area comprises alpine steppe with abundant grasses, sedges, forbs (herbaceous flowering plants) and shrubs (Salix sp., Astragalussp., etc) and the Gyau River flows through the valley where, on 5 August at 4,872 m (30.355°N 81.598°E) we saw a bird which we did not immediately recognise and we obtained images to assist in identification . The presence of a blackish patch on the side of the lower neck/upper breast indicated two possibilities—Bimaculated Lark Melanocorypha bimaculata or Tibetan Lark M. maxima. On careful study, we observed that the bird had a long, comparatively thin bill with a pale pinkish base that turned greyer and darker towards the tip. The long-necked appearance, distinctly rufous rump and the absence of an eyestripe ruled out Bimaculated Lark. In addition, the presence of a white trailing edge to the secondaries and the white sides and broad white tips of the outer tail-feathers supported the identification as Tibetan Lark.